96.6k views
3 votes
-(x + 3) + 3/4x +5= 0​

User Luxuia
by
5.1k points

2 Answers

3 votes

Solution:-


- (x + 3) + (3)/(4x) + 5 = 0


⇒ - x - 3 + (3)/(4x) + 5 = 0


⇒ - x + (3)/(4x) = - 5 + 3


⇒ \frac{ - 4 {x}^(2) + 3 }{4x} = - 2


⇒ - 4 {x}^(2) + 3 = - 8x


⇒ - 4 {x}^(2) + 8x + 3 = 0


⇒4 {x}^(2) - 8x - 3 = 0


⇒x = \frac{ - ( - 8) \pm\sqrt{( - 8)^(2) - 4 * 4 * ( - 3) } }{2 * 4}


⇒x = (8 \pm √(64 + 48) )/(8)


⇒x = (8 \pm √(112) )/(8)


⇒ x_(1) = (8 + √(112) )/(8) \: \: ,\: \: x_(2) = (8 - √(112) )/(8)


⇒ x_(1) = (8 + 10.58)/(8) \: \: , \: \: x_(2) = (8 - 10.58)/(8)


⇒ x_(1) = (18.58)/(8) \: \: , \: \: x_(2) = ( - 2.58)/(8)


⇒ x_(1) = 2.32\: \: , \: \: x_(2) = - 0.32


\sf \red{ \therefore{x_(1) = 2.32\: \: and\: \: x_(2) = - 0.32}}

User Zhou Hongbo
by
4.9k points
0 votes


\text {Hi! Let's Solve this Equation!}


\text {\underline {The First Step is to Simplify}}


\text {-x+-3+3/4x+5=0}\\\text {(-x+3/4x)+(-3+5)=0}


\text {Your New Problem Is: -1/4x+2=0}


\text {\underline {The Next Step Is To Subtract 2}}


\text {-1/4x+2-2=0-2}


\text {Your New Problem Is: -1/4x=-2}


\text {\underline {The Final Step is to Multiply 4/-1}}


\text {4/-1*-1/4x=4/-1*-2}


\text {Your Answer Would Be:}


\fbox {x=8}


\text {Best of Luck!}

User Dumi
by
4.6k points